Budd‐Chiari syndrome on background of JAK2V617F mutation with no hematologic abnormalities. Issue 9 (13th September 2021) - Bint I Bilal, Ammara; Ata, Fateen; Abdelrazek, Mohamed; Yassin, Mohamed A.
Abstract: Whenever considering idiopathic Budd‐Chiari syndrome, consider the possibility of JAK2 mutation even if clinical parameters are within normal range. Abstract : Whenever considering idiopathic Budd‐Chiari syndrome, consider the possibility of JAK2 mutation even if clinical parameters are within normal range.